(untitled) (Comprehensive Journal of Science, 2025)
Background: The increasing frequency and intensity of natural disasters in Libya, exemplified by Storm Daniel’s catastrophic impact on Derna, have exposed critical weaknesses in environmental risk governance and institutional coordination. Despite global frameworks such as the Sendai Framework for Disaster Risk Reduction (2015–2030), empirical research on post-disaster governance and sustainable recovery in the Libyan context remains scarce. Objective: This study aimed to evaluate the effectiveness of environmental risk governance in post-disaster recovery in Derna and to examine how institutional integration, expert participation, multi-level coordination, and multi-sectoral governance influence sustainable reconstruction outcomes. Methods: A cross-sectional descriptive-analytical design was employed involving 250 participants across environmental, engineering, municipal, and academic sectors. Data were collected using a structured Likert-scale questionnaire comprising five variables and analysed using SPSS v29, employing descriptive statistics, Pearson’s correlations, and multiple regression analysis. Results: Findings indicated relatively high agreement on transparency, accountability, and collaborative governance (overall mean = 4.1, SD = 0.7). The strongest predictors of effective governance were multi-sectoral collaboration (r = 0.55, β = 0.47, p < 0.001) and expert participation (r = 0.51, β = 0.42, p < 0.001), while weak multi-level coordination remained a significant challenge (r = –0.37, β = –0.33, p = 0.002). Conclusion: Results highlight that strengthening institutional integration and participatory planning is essential for building resilience and ensuring sustainable recovery in Derna. The study underscores the need for adaptive governance frameworks, enhanced data exchange, and long-term collaboration between government, private, and civil sectors in post-disaster reconstruction.